Long 5' leaders inhibit removal of a 3' trailer from a precursor tRNA by mammalian tRNA 3' processing endoribonuclease. - Nashimoto, M (1999)
Mammalian tRNA 3' processing endoribonuclease (3' tRNase) can remove a 3' trailer from various pre-tRNAs without 5' leader nucleotides. To examine how 5[prime] leader sequences affect 3' processing efficiency, we performed in vitro 3' processing reactions with purified pig 3' tRNase and pre-tRNAArgs containing a 13-nt 3' trailer and a 5[prime] leader of various lengths. The 3' processing was slightly stimulated by 5[prime] leaders containing up to 7 nt, whereas leaders of 9 nt or longer severely inhibited the reaction. Structure probing indicated that the 5' leader sequences had little effect on pre-tRNA folding. Similar results were obtained using pre-tRNA(Val)s containing a 5' leader of various lengths. We also investigated whether 3'tRNase can remove 3' trailers that are stably base-paired with 5' leaders to form an extended acceptor stem. Even such small 5' leaders as 3 and 6 nt, when base-paired with a 3' trailer, severely hindered removal of the 3' trailer by 3' tRNase.